Effectiveness of feeding Maggot (Hermetia illucens) and Biomassa Microalga Aurantiochytrium for The Improvement of Joper Chicken (Gallus dometicus) Productivity - Devi Anugrah; Husnin Nahry Yarza; Muhamad Naufal Afif; Muhammad Adib (Fakultas Keguruan dan Ilmu Pendidikan Universitas Labuhanbatu, 2023)
Maggots and microalgae Aurantiochytrium sp. are known to improve the growth performance of chickens. However, the provision of these two components of chicken feed is still not widely reported. Maggot contains protein, while Aurantiochytium microalgae contain omega 3 DHA, both of which are good for growth. This study aims to determine the effectiveness of feeding joper chickens (Gallus dometicus) with maggot (Hermetia illucens) and Aurantiochytrium. The location of the research will be carried out at the Green House of Muhammadiyah University Prof. DR. Hamka. The study was conducted experiments using Complete Randomized Design (RAL) with 6 treatments and 4 repeats. Treatment P0 (bran and corn 100%), P1 (maggot 10%, microalgae Aurantiochytrium 1.5%, bran & corn 88.5%), P2 (maggot 20%, microalgae Aurantiochytrium 2%, bran & corn 78%), P3 (maggot 30%, microalgae Aurantiochytrium 2.5%, bran & corn 67.5%), P4 (maggot 40%, microalgae Aurantiochytrium 3%, bran & corn 57%), P5 (maggot 50%, microalgae Aurantiochytrium 3.5%, bran & corn 46.5%) The variables observed were body weight and growth in the daily weight rate of joper chickens. The results showed that the effect of variations in the concentration of maggot and Aurantiochytrium microalgae on feed had a significant effect on body weight (P<0.05) and a real effect also (P<0.05) on the daily weight growth rate of joper chickens